Cloud Data Centers and Cost Modeling A Complete Guide To Planning, Designing and Building a Cloud Data Center - Wu, Caesar (Elsevier Science, 2015)
Cloud Data Centers and Cost Modeling establishes a framework for strategic decision-makers to facilitate the development of cloud data centers. Just as building a house requires a clear understanding of the blueprints, architecture, and costs of the project; building a cloud-based data center requires similar knowledge. The authors take a theoretical and practical approach, starting with the key questions to help uncover needs and clarify project scope. They then demonstrate probability tools to test and support decisions, and provide processes that resolve key issues. After laying a foundation of cloud concepts and definitions, the book addresses data center creation, infrastructure development, cost modeling, and simulations in decision-making, each part building on the previous. In this way the authors bridge technology, management, and infrastructure as a service, in one complete guide to data centers that facilitates educated decision making. Explains how to balance cloud computing functionality with data center efficiencyCovers key requirements for power management, cooling, server planning, virtualization, and storage managementDescribes advanced methods for modeling cloud computing cost including Real Option Theory and Monte Carlo SimulationsBlends theoretical and practical discussions with insights for developers, consultants, and analysts considering data center development
Description based on publisher supplied metadata and other sources
Keywords: Cloud computing